A legal status for Avatars in the Metaverse from a Private Law perspective - Arismendy Mengual, Lorena (InDret, 2024)
Avatars, or digital representations of ourselves in the Metaverse are often seen as a fun and unique aspect of virtual worlds, but the legal implications of their use — and potential misuse— remain largely unexplored. In this paper, I address various issues relating to the utilization of avatars in online virtual platforms by individuals, highlighting both their potential benefits advantages and potential problems. In that context, I provide a very much needed clarification of what the Metaverse entails, and I propose a Private Law-oriented framework for thinking and regulating certain aspects of digital avatars in a legally feasible manner.